Organization of Logistic Processes in the Project Activities of Enterprises - Koval Kateryna O.; Iakovenko Vladyslav S.; Kucherenko Serhii K. (Bìznes Inform, 2024)
Today, project activities permeate all areas of the functioning of a traditional industrial enterprise, playing a key role in marketing, research and development, production and sales. In the conditions of a market economy, complex enterprise restructuring projects, which include subprojects for updating the product portfolio, organizational and production restructuring, implementation of financial management and controlling, are of particular importance. The orientation of projects towards achieving certain goals creates a significant internal potential for effective management. The company’s project activities include planning, analysis, implementation, control and evaluation of projects. It helps to improve work efficiency, enhance competitiveness and increase the profitability of the business. An important element is the use of logistic solutions that provide comprehensive services for investment projects. Logistic processes include management of material flows, movement of resources, control, physical distribution of resources, warehousing and optimization of transport and warehouse complexes. The efficiency of logistic processes is determined by several aspects: understanding needs, identifying critical paths and risks, coordinating the supply chain, selecting suppliers, concluding contracts, organizing transportation, routing, tracking, packaging, warehousing, and inventory. In addition, cost control and flexibility of logistic processes are essential for the successful implementation of projects. Project activities require proper coordination of all processes – from planning to monitoring the implementation of tasks. Coordination between different parts of the enterprise, risk management, and sourcing are key aspects of successful project management. Careful organization of project activities allows enterprises to increase work efficiency, competitiveness and achieve their goals.